Pendidikan Ibadah dalam Perspektif Kitab Bulughul Maram Karya Al-Hafidz Ibnu Hajar Al-Asqalani di Pondok Pesantren Nurun ‘Alannur Kapencar Wonosobo - Setia Ningsih; Moh Sakir; Robingun Suyud El Syam (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Worship education is the perfection of faith education, worship education has an important role in shaping a person’s morals and ethics. In this case, worship is not only considered as an obligatory ritual, but also as a means to shape individuals who obey Allah and obey others. Islamic boarding schools that use education based on classical books such as Bulughhul Maram which teach hadiths in the form of worship laws so as to help students understand the essence of worship in their lives. This study aims to analyze worship education in the perspective of the Buluchul Maram book by Al-Hafidz Ibnu Hajar Al-Asqalani, especially in its implementation at the Nurun ‘Alannur 2 Kapencar Wonosobo Islamic Boarding School. This study uses a qualitative field approach. The location of the research taken is the Nurun Alannur Kapencar Wonosobo Islamic Boarding School. The data sources used are primary data and secondary data. Primary data includes the results of interviews and observations. While secondary data is obtained from the results of documentation. Using three data collection techniques, namely interviews, observations, and documentation. Meanwhile, to analyze the data, it is carried out through three stages, namely, data reduction, data presentation, and drawing conclusions. The conclusion of this study. Through literature studies and participatory observations, this study reveals the material on worship education contained in the book and its relevance to the pesantren curriculum. The results of the study show that the Bulughul Maram book makes a significant contribution to worship education and the formation of the character of students through a deep understanding of Islamic law. The material of this book is still relevant and is applied in learning activities in pesantren. However, there are several challenges and opportunities in its implementation. However, by consistently and always developing learning methods on worship education in pesantren, it is hoped that it can improve the quality of worship of students.